Emotional and cognitive barriers of bereavement care among clinical staff in hospice palliative care. Issue 6 (December 2020) - Lin, Wei-Chun; Fan, Sheng-Yu
Abstract: Objective: Bereavement care is one of the major components of hospice palliative care. Previous studies revealed the barriers to the success of the system, including lack of time or support from mental health professionals. Few studies have explored the intrapersonal barriers to bereavement care by clinical staff. The aims of the study were to explore (1) the emotional and cognitive barriers of bereavement care by hospice palliative care staff and (2) the demographic and work characteristics related to these emotional and cognitive barriers. Method: The participants were clinical staff ( n = 301) who were working in hospice palliative care units, including hospice wards, home care, and hospital-based palliative care teams. Their professional backgrounds included physicians ( n = 12), nurses ( n = 172), social workers ( n = 59), psychologists ( n = 34), spiritual care specialists ( n = 15), and others ( n = 9). A cross-sectional design was used and a standardized questionnaire including emotional and cognitive barriers was developed. Information on demographic and work characteristics was also collected. Content validity index, an exploratory factor analysis, and multiple regression analysis were conducted. Results: One emotional barrier, "negative emotional reactions" (13 items, Cronbach's α = 0.92), and three cognitive barriers, "lack of ability" (7 items, Cronbach's α = 0.85), "belief in avoidance" (5 items, Cronbach's α = 0.86), and "outcome expectancy" (4 items, Cronbach's α = 0.85) were identified. Clinical staff who had higher working stress, lower self-rated ability for bereavement care, and higher negative impact from major life loss tended to have higher emotional and cognitive barriers. Significance of results: Clinical staff should be aware of intrapersonal barriers to bereavement care. Educational programs should be developed to improve the ability to engage in bereavement care.